Novel poly(NIPA-co-AAc) functional hydrogels with potential application in drug controlled release - Cuggino, Julio César (2014)
The synthesis, characterization and properties of pH/thermosensitive hydrogels based on acrylic acid (AAc) and N-isopropylacrylamide (NIPA) using (+)-N,N′-diallyltartramide (DAT) as cross-linking agent and water as solvent, are presented in this article. Subsequently, the incorporation of ofloxacin (OFL) as model drug to evaluate the drug load capacity of hydrogels and the in vitro release from OFL-polymer conjugate are presented in order to define potential pharmaceutical applications. Interestingly, the incorporation of AAc diversified the properties of NIPA-based hydrogels allowing ionic interaction of these new materials with drugs of opposite charge and produced different release profiles at pH 1.2 and 6.8 simulated physiological media.